The Regulatory Roadmap: Navigating the FDA Approval Process for Digital Therapeutics (DTx) - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The landscape of modern medicine is undergoing a profound transformation, driven by the convergence of clinical science and cutting-edge software technology....
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Precision Medicine; Machine Learning